Aendronate sodium tablet and preparation method thereof

By using composite disintegrant structure, modified binder and functional surfactant in the preparation process of alendronate sodium tablets, combined with ultra-fine crushing technology and fine granulation process, the problems of slow disintegration speed, low dissolution rate and bioavailability in the preparation process of traditional alendronate sodium tablets are solved, and the uniform distribution and stable release of drug ingredients are achieved, which significantly improves the quality and efficacy of the drug.

CN119792214APending Publication Date: 2025-04-11JIANGSU VANGUARD PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510013106.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The traditional alendronate sodium tablet preparation process has problems such as slow disintegration speed, low dissolution rate and bioavailability, and insufficient uniform distribution of drug components and stable release.

Method used

Specific composite disintegrant structures, modified binders and functional surfactants are adopted, combined with ultra-fine crushing technology and fine granulation process, to ensure rapid disintegration of drugs in the body, high dissolution rate, improved bioavailability, and uniform distribution and stable release of drug ingredients.

Benefits of technology

It significantly improves the dissolution rate and bioavailability of the drug, ensures the uniform distribution and stable release of drug ingredients, improves the quality and efficacy of the drug, and provides patients with a safer and more effective treatment plan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229016620000131
    Figure BDA0005229016620000131
  • Figure BDA0005229016620000132
    Figure BDA0005229016620000132
Patent Text Reader

Abstract

The invention relates to the technical field of pharmaceutical preparations, in particular to an alendronate sodium tablet and a preparation method thereof.The alendronate sodium tablet comprises a tablet core and a coating layer wrapping the tablet core, the tablet core is composed of an active ingredient, a multi-element filler system, a composite disintegrating agent structure, a modified adhesive, a functional surfactant, a customized wetting agent and a composite lubricant, according to the invention, the specific composite disintegrating agent structure is adopted, so that the rapid disintegration of the medicine in the body is realized, the dissolution rate and bioavailability of the medicine are obviously improved, and the well-designed modified adhesive and the functional surfactant act together, so that not only is the cohesion of the medicine particles enhanced, but also the dissolution of the medicine is effectively promoted, and the bioavailability of the medicine is improved. And finally, the preparation process of the alendronate sodium tablet ensures uniform distribution and stable release of medicine components, so that the quality and curative effect of the medicine are improved, and a safer and more effective treatment scheme is provided for patients.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pharmaceutical preparations, in particular to an alendronate sodium tablet and a preparation method thereof. Background Art

[0002] Alendronate sodium is a third-generation bisphosphonate and a new and highly effective bone resorption inhibitor that can inhibit the activity of osteoclasts and reduce bone resorption without directly inhibiting osteoblast activity and bone formation. Oral administration of 10 mg / day or 70 mg / week of alendronate sodium can effectively inhibit bone loss associated with the reduction of endogenous estrogen and is well tolerated. It is a new and alternative treatment for postmenopausal osteoporosis. In the field of pharmaceutical preparation technology, alendronate sodium tablets, as an important therapeutic drug, have always attracted much attention for their quality and efficacy. However, the traditional preparation process of alendronate sodium tablets has many disadvantages, which limits its further development and application.

[0003] First, the disintegrant structure in the traditional preparation process is single, which leads to slow disintegration of the drug in the body, low dissolution rate and bioavailability. Secondly, the selection and design of binders and surfactants are often not targeted and cannot effectively promote drug dissolution while ensuring the cohesion of drug particles. In addition, the traditional preparation process also has shortcomings in the uniform distribution and stable release of drug ingredients, which affects the quality and efficacy of the drug.

[0004] Therefore, a new preparation process of alendronate sodium tablets is urgently needed to solve the above problems and improve the quality and efficacy of the drug. Summary of the invention

[0005] Technical issues solved

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides an alendronate sodium tablet and a preparation method thereof. The present invention realizes the rapid disintegration of the drug in the body by adopting a specific composite disintegrant structure, thereby significantly improving the dissolution rate and bioavailability of the drug. Secondly, the well-designed modified binder and functional surfactant work together to not only enhance the cohesion of the drug particles, but also effectively promote the dissolution of the drug, thereby further improving the absorption efficiency of the drug. Finally, the preparation process of the alendronate sodium tablet ensures the uniform distribution and stable release of the drug components, thereby improving the quality and efficacy of the drug, and providing patients with a safer and more effective treatment plan.

[0007] Technical Solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] In one aspect, an alendronate sodium tablet comprises a tablet core and a coating layer covering the tablet core, wherein the tablet core is composed of an active ingredient, a multi-component filler system, a composite disintegrant structure, a modified binder, a functional surfactant, a customized wetting agent, and a composite lubricant;

[0010] The mass fraction of the active ingredient sodium alendronate is 30%, the mass fraction of the multi-component filler system is 50%, the mass fraction of the composite disintegrant structure is 9%, the mass fraction of the modified binder is 6%, the mass fraction of the functional surfactant is 2%, the amount of the customized wetting agent is determined according to the granulation requirements, and the mass fraction of the composite lubricant is 3%;

[0011] The multi-component filler system is composed of three fillers of different chemical categories and physical properties, namely, hydroxyethyl starch as a starch derivative filler, ethyl cellulose as a cellulose ether filler, and sodium glycinate as an amino acid salt filler, with a mass ratio of 2:1.5:1, the weight average molecular weight of hydroxyethyl starch is 150000-250000Da, the ethoxy content of ethyl cellulose is 45%-47% (w / w), and the particle morphology of sodium glycinate is spherical, with an average particle size of 10-20 μm;

[0012] The composite disintegrant structure comprises an ion exchange resin disintegrant and a swelling disintegrant, the mass ratio of the two being 1.5:1, the ion exchange resin disintegrant being Amberlite IRA-93, having an ion exchange capacity of 0.8-1.2 mmol / g and a particle size range of 50-100 μm, the swelling disintegrant being cross-linked polyvinylpyrrolidone XL-10, having a swelling multiple of 5-8 times in water within 1 minute, and a water absorption rate of 10-15 mL / min, the two disintegrants being present in the tablet core in the form of a core-shell structure, the ion exchange resin disintegrant being the core, and being wrapped by the swelling disintegrant to form a shell;

[0013] The modified adhesive is a product of polyvinyl alcohol after chemical grafting and physical crosslinking treatment, the functional group introduced by chemical grafting is an acrylate group, the grafting rate is 15%-20% (mol / mol), and the physical crosslinking is achieved by electron beam radiation treatment, and the crosslinking degree is 30%-40%;

[0014] The hydrophilic group in the molecular structure of the functional surfactant is a polyoxyethylene group, the hydrophobic group is a combination of a long-chain alkyl group (C12-C16) and a phenyl group, and the HLB value is 12;

[0015] The customized wetting agent is a mixture of ketone, ester and amide solvents in specific proportions, wherein the volume ratio of ketone solvent acetone, ester solvent methyl formate and amide solvent dimethylformamide is 3:1:2, the purity of acetone is more than 99.5%, the purity of methyl formate is more than 99%, and the purity of dimethylformamide is more than 99.8%;

[0016] The composite lubricant is composed of erucic acid amide lubricant and inorganic acid salt lubricant zinc stearate, the mass ratio of the two is 2.5:1, the amide content of erucic acid amide is 95%-98%, and the particle size D50 of zinc stearate is 5-10 μm.

[0017] Furthermore, in the preparation process, hydroxyethyl starch is first pregelatinized at a temperature of 50-60°C and a stirring speed of 50-100 rpm for 30-40 minutes, and then mixed with ethyl cellulose and sodium glycinate in a double-helix cone mixer at a mixing speed of 30-50 rpm for 15-20 minutes to form a uniform multi-component filler system, which is then granulated together with other excipients.

[0018] Furthermore, the added composite disintegrant structure is premixed with alendronate sodium, the multi-component filler system and the modified binder in a ploughshare mixer before granulation, and the premixing parameters are a stirring speed of 130-150 rpm and a premixing time of 11-13 minutes;

[0019] The added composite disintegrant structure is added before the dried particles are mixed with the composite lubricant, using a vacuum drum mixer, the adding method is vacuum suction, the mixing condition is a vacuum degree of 0.05-0.08MPa, and the mixing time is 4-6 minutes.

[0020] Furthermore, the modified binder is placed in a high shear granulator in a powder state with a particle size D90 of 10-20 μm together with other added excipients before granulation, without going through a conventional solution preparation process. Its mechanism of action in the granulation process is to form hydrogen bonds with drug molecules through chemically grafted acrylate groups, and the physical cross-linking structure enhances the cohesion of the particles. The interaction mode with other excipients has been redesigned, so that the tablet core strength is ensured while facilitating drug release.

[0021] Furthermore, during granulation, the functional surfactant is dissolved in the customized wetting agent. The dissolution process uses a planetary agitator with a stirring speed of 30-40rpm and a stirring time of 4-5 minutes to ensure that it is completely dissolved and evenly dispersed in the customized wetting agent. It is then added to the granulator and mixed with other materials for granulation. Its distribution state in the tablet core is in the form of a monolayer and micelles on the surface of the drug particles. The promotion of drug dissolution is achieved by reducing the interfacial tension between the drug and the solvent and forming inclusion complexes with the drug molecules.

[0022] Furthermore, before mixing, acetone needs to be purified by a distillation tower, methyl formate and dimethylformamide are purified by molecular distillation technology, and when mixing, gradual dropwise addition and slow stirring are adopted, with a stirring speed of 15-20rpm and a temperature controlled at 20-25°C to ensure uniform mixing, and then used for granulation. The wetting property of the material is achieved by reducing the surface energy of the material, and the effect on drug release is to adjust the dissolution rate of the drug.

[0023] Furthermore, erucic acid amide needs to be heated at 70-80° C. for 10-15 minutes before use to soften it, and zinc stearate needs to be surface treated with a silane coupling agent before use, and the amount of the silane coupling agent used is 0.5%-1% of the mass of zinc stearate;

[0024] During the total mixing process, the dried and granulated particles are first mixed with the added composite disintegrant structure in a V-type mixer for 9-11 minutes at a speed of 11-13 rpm, and then the treated erucic acid amide and zinc stearate are added and continued to mix. A three-dimensional motion mixer is used. The mixing process is first low-speed mixing for 3-4 minutes at a speed of 6-8 rpm, and then high-speed mixing for 3-5 minutes at a speed of 10-12 rpm to ensure that the composite lubricant is evenly distributed in the tablet core without affecting other properties of the tablet core.

[0025] On the other hand, the preparation method of alendronate sodium tablets comprises the following steps:

[0026] First, the sodium alendronate raw material is crushed to a particle size D90 of 8-12 μm by ultrafine grinding technology. The ultrafine grinding technology is based on the principle of supersonic airflow impact and collision, with an airflow velocity of 350-450 m / s and is carried out under argon protection with an argon flow rate of 9-11 L / min.

[0027] Then, the crushed alendronate sodium, the multi-component filler system, the added composite disintegrant structure and the modified binder are placed in a granulating device with a double-shaft paddle stirring structure for premixing. The premixing parameters are a stirring speed of 130-150 rpm and a premixing time of 11-13 minutes. The design of the stirring structure ensures that the materials can be fully mixed and avoids local overheating.

[0028] Next, the functional surfactant is dissolved in the customized wetting agent, stirred at a speed of 30-40 rpm for 4-5 minutes to make it evenly dissolved, and added to the granulator. The granulation parameters are stirring speed 160-180 rpm, shear speed 600-800 rpm, and granulation time 11-14 minutes to obtain wet granules. The wet granules are dried by pulse vacuum drying equipment at a drying temperature of 32-38°C, a vacuum pulse frequency of 0.5-1.0 Hz, and an amplitude of 0.03-0.06 MPa until the moisture content of the granules is between 0.5% and 0.8%. The dried granules are sized using a 21-23 mesh screen;

[0029] The granules after granulation are placed in a fluidized bed mixer with a forced convection function, and the additional composite disintegrant structure is first added, mixed for 9-11 minutes at a speed of 11-13 rpm, and then the composite lubricant is added, and the mixing is continued for 7-8 minutes at a speed of 9-11 rpm to obtain the total mixed granules;

[0030] Finally, the total mixed granules are compressed with a φ8mm biconvex circular punch, the compression pressure is 110-130 kN, the compression speed is 22-28 rpm, and plain tablets are obtained. The plain tablets are then placed in a coating device using the centrifugal atomization principle, and coated with a pH-responsive film coating material, the coating solution concentration is 11%-13%, and the coating weight gain is 2.5%-3.5%, thereby obtaining alendronate sodium tablets.

[0031] Furthermore, during the drying process of the pulse vacuum drying equipment, the heating method is microwave-assisted heating, the microwave power is 1.5-2.5kW, and the material is laid in the drying chamber at a thickness of 2-3cm to ensure drying uniformity;

[0032] In the coating equipment that adopts the centrifugal atomization principle, the atomizing disk speed is 1800-2200rpm, the inlet air temperature is 42-48℃, the outlet air temperature is 28-32℃, the atomizing air pressure is 0.2-0.25MPa, and the deposition uniformity of the coating material is controlled by the air flow distribution system during the coating process. The air flow velocity is 0.3-0.5m / s, and the direction is at an angle of 30-60° with the movement direction of the tablet core, which is dynamically adjusted according to the movement state of the tablet core.

[0033] Beneficial Effects

[0034] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0035] 1. The present invention significantly improves the dissolution rate of the drug by adopting a specific composite disintegrant structure, namely a core-shell structure composed of an ion exchange resin disintegrant Amberlite IRA-93 and a swelling disintegrant cross-linked polyvinylpyrrolidone XL-10. The ion exchange resin disintegrant as the inner core can quickly absorb water and swell to generate internal pressure, thereby prompting the tablet to disintegrate rapidly. The swelling disintegrant as the outer shell further enhances the disintegration effect, thereby enabling the drug components to be released into the body fluid more quickly.

[0036] 2. The present invention uses ultrafine grinding technology to grind the alendronate sodium raw material to a particle size D90 of 8-12 μm, thereby improving the fineness and uniformity of the drug. At the same time, a granulating device with a double-shaft paddle stirring structure is used for premixing and granulation, ensuring that the materials can be fully mixed and avoiding local overheating, thereby improving the uniformity and stability of the tablets. In addition, the use of pulse vacuum drying equipment and microwave-assisted heating methods further improves the drying efficiency and drying uniformity, ensuring that the moisture content of the tablets meets the standard. These optimization measures jointly improve the quality of the tablets, making them have better stability and reliability.

[0037] 3. The present invention adopts a pH-responsive film coating material for coating, which not only improves the stability and moisture resistance of the tablets, but also improves the taste of the drug. The selection of coating materials and the optimization of coating processes enable the tablets to quickly release drug ingredients when they dissolve in the mouth, while reducing irritation to the oral cavity and esophagus. In addition, the coating material also has a certain taste-masking effect, which can cover up the unpleasant taste of the drug, thereby improving the patient's compliance and medication experience. These improvements help to increase patient acceptance and satisfaction with the drug, and improve the treatment effect and the patient's quality of life. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention will be further described below in conjunction with the embodiments.

[0040] Embodiment 1:

[0041] 1. Raw material preparation:

[0042] Alendronate sodium raw material: using ultrafine grinding technology, based on the principle of supersonic airflow impact and collision, at an airflow velocity of 400m / s, an argon flow rate of 10L / min and argon protection, the alendronate sodium raw material was crushed to a particle size D90 of 10μm.

[0043] Multi-component filler system:

[0044] Hydroxyethyl starch: Hydroxyethyl starch with a weight average molecular weight of 200,000 Da was selected and pregelatinized at 55° C. and a stirring speed of 80 rpm for 35 minutes.

[0045] Ethyl cellulose: Ethyl cellulose with an ethoxy content of 46% (w / w).

[0046] Sodium glycinate: The particle shape of sodium glycinate is spherical and the average particle size is 15 μm. Pregelatinized hydroxyethyl starch is mixed with ethyl cellulose and sodium glycinate in a double-helix conical mixer at a mass ratio of 2:1.5:1. The mixing speed is 40 rpm and the mixing time is 18 minutes to form a uniform multi-component filler system.

[0047] Composite disintegrant structure:

[0048] Ion exchange resin disintegrant Amberlite IRA-93: The ion exchange capacity is 1.0 mmol / g and the particle size range is 70 μm.

[0049] Swelling disintegrant cross-linked polyvinylpyrrolidone XL-10: It swells 6 times in water within 1 minute and has a water absorption rate of 12 mL / min. The two are mixed at a mass ratio of 1.5:1 and exist in the form of a core-shell structure. The ion exchange resin type disintegrant serves as the core and is wrapped by the swelling disintegrant to form a shell. The internal composite disintegrant structure is premixed with sodium alendronate, a multi-component filler system and a modified binder in a plowshare mixer before granulation. The premixing parameters are a stirring speed of 140 rpm and a premixing time of 12 minutes. The external composite disintegrant structure is added before the dried particles are mixed with the composite lubricant. A vacuum drum mixer is used for vacuum suction with a vacuum degree of 0.06 MPa and a mixing time of 5 minutes.

[0050] Modified adhesive: Polyvinyl alcohol was chemically grafted with acrylic acid ester groups (grafting rate was 18% (mol / mol)), and then physically cross-linked (cross-linking degree was 35%) by electron beam radiation treatment to obtain a modified adhesive, which was put into a high shear granulator together with other internal auxiliary materials in a powder state with a particle size D90 of 15 μm before granulation.

[0051] Functional surfactant: The hydrophilic group in the molecular structure is polyoxyethylene, the hydrophobic group is a combination of long-chain alkyl (C12-C16) and phenyl, and the HLB value of the functional surfactant is 12. It is dissolved in a customized wetting agent and a planetary stirrer is used with a stirring speed of 35 rpm and a stirring time of 4.5 minutes to ensure complete dissolution and uniform dispersion. The customized wetting agent is a mixture of acetone (purity above 99.5%), methyl formate (purity above 99%) and dimethylformamide (purity above 99.8%) in a volume ratio of 3:1:2. The acetone is purified by a distillation tower, and methyl formate and dimethylformamide are purified by molecular distillation technology. During mixing, they are gradually added dropwise and stirred slowly (stirring speed 18 rpm, temperature 23°C).

[0052] Composite lubricant:

[0053] Erucic acid amide: The amide content is 96%. It is heated at 75°C for 12 minutes to soften it before use.

[0054] Zinc stearate: The particle size D50 is 8 μm, and the surface is treated with a silane coupling agent (the amount used is 0.8% of the mass of zinc stearate) before use, and the mass ratio of the two is 2.5:1.

[0055] 2. Granulation:

[0056] The crushed alendronate sodium, multi-filler system, internal composite disintegrant structure and modified binder were placed in a granulating device with a double-shaft paddle stirring structure for premixing at a stirring speed of 140 rpm and a premixing time of 12 minutes. Then, a customized wetting agent dissolved with a functional surfactant was added to the granulator. The granulation parameters were a stirring speed of 170 rpm, a shear speed of 700 rpm and a granulation time of 12 minutes to obtain wet granules.

[0057] 3. Drying and granulation:

[0058] The wet granules were dried by pulse vacuum drying equipment (microwave assisted heating, microwave power of 2 kW, material paving thickness of 2.5 cm), the drying temperature was 35°C, the vacuum pulse frequency was 0.8 Hz, the amplitude was 0.05 MPa, and the granules were dried to a moisture content of 0.6%, and granulated with a 22-mesh screen.

[0059] 4. Total mixing:

[0060] The granules after granulation were placed in a fluidized bed mixer with forced convection function, and the additional composite disintegrant structure was first added and mixed for 10 minutes at a speed of 12 rpm, and then the composite lubricant was added and mixed for 7.5 minutes at a speed of 10 rpm to obtain the total mixed granules.

[0061] 5. Tablet compression and coating:

[0062] The total mixed granules were tableted using a φ8mm biconvex circular punch die with a tableting pressure of 120 kN and a tableting speed of 25 rpm to obtain plain tablets, which were then placed in a coating device using the centrifugal atomization principle (the atomizing disk speed was 2000 rpm, the inlet air temperature was 45°C, the outlet air temperature was 30°C, the atomizing air pressure was 0.22 MPa, the air flow velocity was 0.4 m / s, and the direction was at an angle of 45° to the movement direction of the tablet core), and coated with a pH-responsive film coating material, the coating solution concentration was 12%, and the coating weight gain was 3%, to obtain alendronate sodium tablets.

[0063] Embodiment 2:

[0064] 1. Raw material preparation:

[0065] Alendronate sodium raw material: using ultrafine grinding technology, at an air flow velocity of 350m / s, an argon flow rate of 9L / min and under argon protection, the alendronate sodium raw material was ground to a particle size D90 of 8μm.

[0066] Multi-component filler system:

[0067] Hydroxyethyl starch: weight average molecular weight is 150000 Da, and pregelatinization treatment is performed at 50° C. and stirring speed is 50 rpm for 30 minutes.

[0068] Ethyl cellulose: ethoxy content is 45% (w / w).

[0069] Sodium glycinate: The average particle size is 10 μm, and the mixture is mixed in a double-helix cone mixer at a mass ratio of 2:1.5:1, with a mixing speed of 30 rpm and a mixing time of 15 minutes.

[0070] Composite disintegrant structure:

[0071] Ion exchange resin disintegrant Amberlite IRA-93: The ion exchange capacity is 0.8 mmol / g and the particle size range is 50 μm.

[0072] Swellable disintegrant cross-linked polyvinylpyrrolidone XL-10: The swelling ratio in water is 5 times within 1 minute, the water absorption rate is 10 mL / min, and the mixture is mixed at a mass ratio of 1.5:1. The premixing and addition conditions are the same as those in Example 1.

[0073] Modified adhesive: polyvinyl alcohol grafted with acrylic acid ester groups (grafting rate of 15% (mol / mol)), physically crosslinked (crosslinking degree of 30%), and granulated in a powder state with a particle size D90 of 10 μm.

[0074] Functional surfactant: dissolved in a customized wetting agent (mixing method is the same as in Example 1), the composition and processing method of the customized wetting agent are the same as in Example 1.

[0075] Composite lubricant:

[0076] Erucic acid amide: amide content is 95%, heating treatment at 70℃ for 10 minutes.

[0077] Zinc stearate: The particle size D50 is 5 μm, the amount of silane coupling agent used is 0.5% of the mass of zinc stearate, and the mass ratio of the two is 2.5:1.

[0078] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0079] The granulation parameters were stirring speed 160 rpm, shear speed 600 rpm, and granulation time 11 min;

[0080] The drying temperature was 32°C, the vacuum pulse frequency was 0.5 Hz, the amplitude was 0.03 MPa, the moisture content of the granules was 0.5%, and the granules were sized using a 21-mesh screen;

[0081] In a fluidized bed mixer, disintegrants were first added and mixed for 9 minutes at a speed of 11 rpm, and lubricants were then added and mixed for 7 minutes at a speed of 9 rpm;

[0082] The tableting pressure is 110kN and the tableting speed is 22 rpm; the coating equipment parameters are as follows: the atomizing disk speed is 1800rpm, the inlet air temperature is 42°C, the outlet air temperature is 28°C, the atomizing air pressure is 0.2MPa, the air flow velocity is 0.3m / s, the direction is 30° with the direction of tablet core movement, the coating liquid concentration is 11%, and the coating weight gain is 2.5%.

[0083] Embodiment three:

[0084] 1. Raw material preparation:

[0085] Alendronate sodium raw material: using ultrafine grinding technology, at an air flow velocity of 450m / s, an argon flow rate of 11L / min and under argon protection, the alendronate sodium raw material was ground to a particle size D90 of 12μm.

[0086] Multi-component filler system:

[0087] Hydroxyethyl starch: weight average molecular weight is 250000 Da, and pregelatinization treatment is performed at 60° C. and stirring speed is 100 rpm for 40 minutes.

[0088] Ethyl cellulose: ethoxy content is 47% (w / w).

[0089] Sodium glycinate: The average particle size is 20 μm, and the mixture is mixed in a double-helix cone mixer at a mass ratio of 2:1.5:1, with a mixing speed of 50 rpm and a mixing time of 20 minutes.

[0090] Composite disintegrant structure:

[0091] Ion exchange resin disintegrant Amberlite IRA-93: The ion exchange capacity is 1.2 mmol / g and the particle size range is 100 μm.

[0092] Swellable disintegrant cross-linked polyvinylpyrrolidone XL-10: The swelling ratio in water is 8 times within 1 minute, the water absorption rate is 15 mL / min, and the mixture is mixed at a mass ratio of 1.5:1. The premixing and addition conditions are the same as those in Example 1.

[0093] Modified adhesive: polyvinyl alcohol grafted with acrylic acid ester groups (grafting rate of 20% (mol / mol)), physically crosslinked (crosslinking degree of 40%), and granulated in a powder state with a particle size D90 of 20 μm.

[0094] Functional surfactant: dissolved in a customized wetting agent (mixing method is the same as in Example 1), the composition and processing method of the customized wetting agent are the same as in Example 1.

[0095] Composite lubricant:

[0096] Erucic acid amide: amide content is 98%, heating treatment is carried out at 80℃ for 15 minutes.

[0097] Zinc stearate: The particle size D50 is 10 μm, the amount of silane coupling agent used is 1% of the mass of zinc stearate, and the mass ratio of the two is 2.5:1.

[0098] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0099] The granulation parameters were stirring speed 180 rpm, shear speed 800 rpm, and granulation time 14 min;

[0100] The drying temperature was 38°C, the vacuum pulse frequency was 1.0 Hz, the amplitude was 0.06 MPa, the moisture content of the granules was 0.8%, and the granules were sized using a 23-mesh sieve;

[0101] In a fluidized bed mixer, disintegrants were first added and mixed for 11 minutes at a speed of 13 rpm, and lubricants were then added and mixed for 8 minutes at a speed of 11 rpm;

[0102] The tableting pressure is 130kN and the tableting speed is 28 rpm; the coating equipment parameters are as follows: the atomizing disk speed is 2200rpm, the inlet air temperature is 48°C, the outlet air temperature is 32°C, the atomizing air pressure is 0.25MPa, the air flow velocity is 0.5m / s, the direction is 60° with the movement direction of the tablet core, the coating liquid concentration is 13%, and the coating weight gain is 3.5%.

[0103] Comparative Example 1 (Changing the Multi-component Filler System):

[0104] 1. Raw material preparation:

[0105] A single filler, microcrystalline cellulose, was used to replace the multi-filler system. Other raw materials were prepared in the same manner as in Example 1, but operations related to the multi-filler system, such as pregelatinization of hydroxyethyl starch, were not performed.

[0106] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0107] The granulation parameters, drying conditions, granulation screen, total mixing conditions, tableting parameters and coating conditions are the same as those in Example 1.

[0108] Comparative Example 2 (Changing the structure of the composite disintegrant):

[0109] 1. Raw material preparation:

[0110] A single disintegrant, sodium carboxymethyl starch, was used to replace the composite disintegrant structure, and different treatment operations of internal and external disintegrants were not performed. Other raw materials were prepared in the same manner as in Example 1.

[0111] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0112] The granulation parameters, drying conditions, granulation screen, total mixing conditions, tableting parameters and coating conditions are the same as those in Example 1.

[0113] Comparative Example 3 (changing the modified adhesive):

[0114] 1. Raw material preparation:

[0115] Ordinary polyvinyl alcohol was used as the adhesive without chemical grafting and physical cross-linking treatment. Other raw materials were prepared in the same manner as in Example 1.

[0116] 2. Granulation, drying, granulation, mixing, tableting and packaging:

[0117] The granulation parameters, drying conditions, granulation screen, total mixing conditions, tableting parameters and coating conditions are the same as those in Example 1.

[0118] Comparative Example 4 (changing the functional surfactant):

[0119] 1. Raw material preparation:

[0120] Sodium dodecyl sulfate was used as a surfactant, and was directly mixed with other raw materials without being dissolved in a customized wetting agent. The other raw materials were prepared in the same manner as in Example 1.

[0121] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0122] The granulation parameters, drying conditions, granulation screen, total mixing conditions, tableting parameters and coating conditions are the same as those in Example 1.

[0123] Comparative Example 5 (Changing the Composite Lubricant):

[0124] 1. Raw material preparation:

[0125] Magnesium stearate was used as a single lubricant to replace the composite lubricant, erucamide heating and zinc stearate surface treatment were not performed, and other raw materials were prepared in the same manner as in Example 1.

[0126] 2. Granulation, drying, granulation, mixing, tableting and coating:

[0127] The granulation parameters, drying conditions, granulation screen, total mixing conditions, tableting parameters and coating conditions are the same as those in Example 1.

[0128] Experimental example:

[0129] 1. Core quality evaluation:

[0130] Hardness test: The hardness of the tablet cores obtained in each embodiment and comparative example was tested using a tablet hardness tester. The results are shown in Table 1 below;

[0131] Friability test: Friability was measured according to the pharmacopoeia method, and the results are shown in Table 1 below;

[0132] Disintegration time test: The disintegration time was measured using a disintegration apparatus. The results are shown in Table 1 below.

[0133] 2. Drug dissolution test:

[0134] The dissolution rate of the drug in each example and comparative example at different time points was measured using a dissolution tester with pH 4.5 acetate buffer as the dissolution medium. The results are shown in Table 2 below.

[0135] Table 1:

[0136]

[0137] Table 2:

[0138]

[0139] It can be seen from the above experimental results that the alendronate sodium tablets prepared in Examples 1, 2 and 3 of the present invention are superior to those in Comparative Example 1, 2, 3, 4 and 5 in terms of tablet core quality (hardness, friability, disintegration time) and drug solubility.

[0140] In terms of hardness, the hardness of Example 1, Example 2 and Example 3 is above 145N, while the hardness of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 is relatively low;

[0141] In terms of disintegration time, the disintegration time of Example 1, Example 2 and Example 3 were all within 4 minutes, while that of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 was longer;

[0142] In terms of drug dissolution, the dissolution rates of Example 1, Example 2 and Example 3 at each time point were higher than those of Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5.

[0143] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An alendronate sodium tablet, characterized in that: The invention comprises a tablet core and a coating layer for coating the tablet core, wherein the tablet core is composed of an active ingredient, a multi-component filler system, a composite disintegrant structure, a modified binder, a functional surfactant, a customized wetting agent and a composite lubricant; The mass fraction of the active ingredient sodium alendronate is 30%, the mass fraction of the multi-component filler system is 50%, the mass fraction of the composite disintegrant structure is 9%, the mass fraction of the modified binder is 6%, the mass fraction of the functional surfactant is 2%, the amount of the customized wetting agent is determined according to the granulation requirements, and the mass fraction of the composite lubricant is 3%; The multi-component filler system is composed of three fillers of different chemical categories and physical properties, namely, hydroxyethyl starch as a starch derivative filler, ethyl cellulose as a cellulose ether filler, and sodium glycinate as an amino acid salt filler, with a mass ratio of 2:1.5:1, the weight average molecular weight of hydroxyethyl starch is 150000-250000Da, the ethoxy content of ethyl cellulose is 45%-47% (w / w), and the particle morphology of sodium glycinate is spherical, with an average particle size of 10-20 μm; The composite disintegrant structure comprises an ion exchange resin disintegrant and a swelling disintegrant, the mass ratio of the two being 1.5:1, the ion exchange resin disintegrant being Amberlite IRA-93, having an ion exchange capacity of 0.8-1.2 mmol / g and a particle size range of 50-100 μm, the swelling disintegrant being cross-linked polyvinylpyrrolidone XL-10, having a swelling multiple of 5-8 times in water within 1 minute, and a water absorption rate of 10-15 mL / min, the two disintegrants being present in the tablet core in the form of a core-shell structure, the ion exchange resin disintegrant being the core, and being wrapped by the swelling disintegrant to form a shell; The modified adhesive is a product of polyvinyl alcohol after chemical grafting and physical crosslinking treatment, the functional group introduced by chemical grafting is an acrylate group, the grafting rate is 15%-20% (mol / mol), and the physical crosslinking is achieved by electron beam radiation treatment, and the crosslinking degree is 30%-40%; The hydrophilic group in the molecular structure of the functional surfactant is a polyoxyethylene group, the hydrophobic group is a combination of a long-chain alkyl group (C12-C16) and a phenyl group, and the HLB value is 12; The customized wetting agent is a mixture of ketone, ester and amide solvents in specific proportions, wherein the volume ratio of ketone solvent acetone, ester solvent methyl formate and amide solvent dimethylformamide is 3:1:2, the purity of acetone is more than 99.5%, the purity of methyl formate is more than 99%, and the purity of dimethylformamide is more than 99.8%; The composite lubricant is composed of erucic acid amide lubricant and inorganic acid salt lubricant zinc stearate, the mass ratio of the two is 2.5:1, the amide content of erucic acid amide is 95%-98%, and the particle size D50 of zinc stearate is 5-10 μm.

2. The alendronate sodium tablet according to claim 1, characterized in that: During the preparation process, hydroxyethyl starch is first pregelatinized at a temperature of 50-60°C and a stirring speed of 50-100 rpm for 30-40 minutes, and then mixed with ethyl cellulose and sodium glycinate in a double-helix cone mixer at a mixing speed of 30-50 rpm for 15-20 minutes to form a uniform multi-component filler system, which is then granulated together with other excipients.

3. The alendronate sodium tablet according to claim 1, characterized in that: The added composite disintegrant structure is premixed with alendronate sodium, a multi-component filler system and a modified binder in a ploughshare mixer before granulation, and the premixing parameters are a stirring speed of 130-150 rpm and a premixing time of 11-13 minutes; The added composite disintegrant structure is added before the dried particles are mixed with the composite lubricant, using a vacuum drum mixer, the adding method is vacuum suction, the mixing condition is a vacuum degree of 0.05-0.08MPa, and the mixing time is 4-6 minutes.

4. The alendronate sodium tablet according to claim 1, characterized in that: The modified adhesive is placed in a high shear granulator in a powder state with a particle size D90 of 10-20 μm together with other internal auxiliary materials before granulation, without going through a conventional solution preparation process. Its mechanism of action in the granulation process is to form hydrogen bonds with drug molecules through chemically grafted acrylate groups, and the physical cross-linking structure enhances the cohesion of the particles.

5. The alendronate sodium tablet according to claim 1, characterized in that: During granulation, the functional surfactant is dissolved in the customized wetting agent. The dissolution process uses a planetary agitator with a stirring speed of 30-40rpm and a stirring time of 4-5 minutes to ensure that it is completely dissolved and evenly dispersed in the customized wetting agent. It is then added to the granulator and mixed with other materials for granulation. Its distribution state in the tablet core is in the form of a monolayer and micelles on the surface of the drug particles. The promotion of drug dissolution is achieved by reducing the interfacial tension between the drug and the solvent and forming inclusion complexes with the drug molecules.

6. The alendronate sodium tablet according to claim 1, characterized in that: Before mixing, acetone needs to be purified by a distillation tower, and methyl formate and dimethylformamide are purified by molecular distillation technology. When mixing, gradual dropwise addition and slow stirring are adopted, and the stirring speed is 15-20rpm. The temperature is controlled at 20-25°C to ensure uniform mixing, and then it is used for granulation. The wetting performance of the material is achieved by reducing the surface energy of the material, and the effect on drug release is to adjust the dissolution rate of the drug.

7. The alendronate sodium tablet according to claim 1, characterized in that: Erucic acid amide needs to be heated at 70-80°C for 10-15 minutes before use to soften it. Zinc stearate needs to be surface treated with a silane coupling agent before use. The amount of the silane coupling agent is 0.5%-1% of the mass of zinc stearate. During the total mixing process, the dried and granulated particles are first mixed with the added composite disintegrant structure in a V-type mixer for 9-11 minutes at a speed of 11-13 rpm, and then the treated erucic acid amide and zinc stearate are added and continued to mix. A three-dimensional motion mixer is used. The mixing process is first low-speed mixing for 3-4 minutes at a speed of 6-8 rpm, and then high-speed mixing for 3-5 minutes at a speed of 10-12 rpm to ensure that the composite lubricant is evenly distributed in the tablet core without affecting other properties of the tablet core.

8. The method for preparing the alendronate sodium tablets according to any one of claims 1 to 7, characterized in that: The reforming method comprises the following steps: First, the sodium alendronate raw material is crushed to a particle size D90 of 8-12 μm by ultrafine grinding technology. The ultrafine grinding technology is based on the principle of supersonic airflow impact and collision, with an airflow velocity of 350-450 m / s and is carried out under argon protection with an argon flow rate of 9-11 L / min. Then, the crushed alendronate sodium, the multi-component filler system, the added composite disintegrant structure and the modified binder are placed in a granulating device with a double-shaft paddle stirring structure for premixing, and the premixing parameters are a stirring speed of 130-150 rpm and a premixing time of 11-13 minutes; Next, the functional surfactant is dissolved in the customized wetting agent, stirred at a speed of 30-40 rpm for 4-5 minutes to make it evenly dissolved, and added to the granulator. The granulation parameters are stirring speed 160-180 rpm, shear speed 600-800 rpm, and granulation time 11-14 minutes to obtain wet granules. The wet granules are dried by pulse vacuum drying equipment at a drying temperature of 32-38°C, a vacuum pulse frequency of 0.5-1.0 Hz, and an amplitude of 0.03-0.06 MPa until the moisture content of the granules is between 0.5% and 0.8%. The dried granules are sized using a 21-23 mesh screen; The granules after granulation are placed in a fluidized bed mixer with a forced convection function, and the additional composite disintegrant structure is first added, mixed for 9-11 minutes at a speed of 11-13 rpm, and then the composite lubricant is added, and the mixing is continued for 7-8 minutes at a speed of 9-11 rpm to obtain the total mixed granules; Finally, the total mixed granules are compressed with a φ8mm biconvex circular punch, the compression pressure is 110-130 kN, the compression speed is 22-28 rpm, and plain tablets are obtained. The plain tablets are then placed in a coating device using the centrifugal atomization principle, and coated with a pH-responsive film coating material, the coating solution concentration is 11%-13%, and the coating weight gain is 2.5%-3.5%, thereby obtaining alendronate sodium tablets.

9. The method for preparing alendronate sodium tablets according to claim 8, characterized in that: During the drying process of the pulse vacuum drying equipment, the heating method is microwave-assisted heating, the microwave power is 1.5-2.5kW, and the material is laid in the drying chamber with a thickness of 2-3cm; In the coating equipment that adopts the centrifugal atomization principle, the atomizing disk speed is 1800-2200rpm, the inlet air temperature is 42-48℃, the outlet air temperature is 28-32℃, the atomizing air pressure is 0.2-0.25MPa, and the deposition uniformity of the coating material is controlled by the air flow distribution system during the coating process. The air flow velocity is 0.3-0.5m / s, and the direction is at an angle of 30-60° with the movement direction of the tablet core, which is dynamically adjusted according to the movement state of the tablet core.